Heart failure is the strongest predictor of acute kidney injury in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction - Matějka, Jan; Varvařovský, Ivo; Rozsíval, Vladimír; Herman, Aleš; Bláha, K.; Večeřa, J.; Lazarák, Tomáš; Novotný, V.; Mužáková, Vladimíra; Vojtíšek, Petr (My University, 2016)
BACKGROUND: ST elevation myocardial infarction (STEMI) patients treated by primary PCI are at high risk of acute kidney injury (AKI). AIM: To evaluate incidence, risk factors and consequences of AKI in patients undergoing primary PCI. METHODS: Retrospective analysis. RESULTS: 202 patients included. AKI occurred in 25 (12.4%) of them. Characteristics of the patients with and without AKI did not differ significantly except for age (69 ± 13 vs. 62 ± 12;p=0.003), female gender (48.0% vs. 26.6%; p=0.035), hypertension (88.0% vs.62.7%; p=0.013), LV ejection fraction (40% ± 12% vs. 49% ± 14%; p=0.002),cardiogenic shock (44.0% vs. 5.1 %; p<0.0001) and in-hospital mortality (24.0% vs. 3.4%; p=0.001). In multivariate analysis heart failure remained the only independent correlate of AKI. CONCLUSIONS: Heart failure was the strongest predictor of AKI. Other risks factors including contrast medium volume, baseline renal function, diabetes and age failed to predict AKI.
Srdeční selhání je nejsilnějším prediktorem akutního poškození ledvin u pacientů podstupujících primární perkutánní koronární intervenci pro akutní infarkt myokardu s ST elevacemi
Keywords: acute kidney injury; contrast-induced acute kidney injury; STEMI; primary PCI; complication; akutní poškození ledvin; kontrastem indukované akutní poškození ledvin; STEMI; primární PCI; komplikace